Positive Affirmations in the Lives of Generation Z - Syahadah, Amrina Ghina; Yuliana, Nina (SEAN Institute, 2024)
Positive affirmations are positive statements or sentences expressed to the subconscious mind or in the form of writing to express a goal. Affirmation statements must be positive and in line with what you believe within yourself. Usually, affirmations are done repeatedly so that they are effective. Currently, many Generation Z are implementing positive affirmations into their lives. This phenomenon is very interesting to find out more deeply. This research wants to find out how affirmations are in the lives of Generation Z. The aim of the research is to find out whether positive affirmations can feel love and affection, can form interactions with other individuals, and can also respect yourself. The theory used in this research is the theory of motivation proposed by Abraham Maslow. The paradigm of this research is post-positivism. The research method used is a qualitative descriptive research method where data collection is carried out by interviewing informants who meet the criteria. The results of this research show that each individual has their own way of carrying out positive affirmation activities. Apart from that, positive affirmations can also make someone love themselves more, can make interpersonal communication smoother without obstacles, and can make someone respect themselves more because negative thoughts within themselves are reduced or even erased in the individual's mind.